2015
DOI: 10.1177/229255031502300413
|View full text |Cite
|
Sign up to set email alerts
|

Use of tranexamic acid in craniosynostosis surgery

Abstract: TXA decreased blood product transfusion requirements in patients undergoing CVR for sagittal craniosynostosis, and should be a routine part of the strategy to reduce blood loss in these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
2
32
3
Order By: Relevance
“…Furthermore, no trial specifically compared TXA efficacy between each craniosynostosis operation. [21][22][23][24][25][26][27] This is potentially a major confounder; by extrapolation of the findings of Howe and Cooper, there is potentially a significant clinical variation in TXA-mediated blood loss reduction between the different craniosynostosis operations. Given FOR and CVR are known to involve significantly more blood loss and require more transfusions than the less invasive techniques such as SC and PVE, it is reasonable to presume that the clinical benefit of TXA would be far more evident in FOR and CVR procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no trial specifically compared TXA efficacy between each craniosynostosis operation. [21][22][23][24][25][26][27] This is potentially a major confounder; by extrapolation of the findings of Howe and Cooper, there is potentially a significant clinical variation in TXA-mediated blood loss reduction between the different craniosynostosis operations. Given FOR and CVR are known to involve significantly more blood loss and require more transfusions than the less invasive techniques such as SC and PVE, it is reasonable to presume that the clinical benefit of TXA would be far more evident in FOR and CVR procedures.…”
Section: Discussionmentioning
confidence: 99%
“…34 While Ausen et al 34 investigated a different elective procedure and method of drug delivery, their results mirror our own and revealed that blood loss may also be reduced after surgery in a more invasive elective cosmetic procedure. In the pediatric literature, a number of high-quality studies [35][36][37][38][39][40] investigating the role of tranexamic acid in craniosynostosis procedures have consistently shown that tranexamic acid reduces both intraoperative blood loss and rates of transfusion. The benefits of tranexamic acid in burn surgery are similarly promising 41,42 ; however, more studies are needed before determining causality, dosing regimens, and contraindications in this acutely ill population.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies were eligible for our review. Of the 13 studies, 4 were prospective, randomized, double-blind controlled trials [9,10,14,15], 9 were retrospective studies, tailored as a "before-after" studies, comparing blood loss and transfusion without/with TXA [16][17][18][19][20][21][22][23][24]. Study characteristics are presented in Table 1 and 2.…”
Section: Selection Of Reports and Study Designmentioning
confidence: 99%
“…A loading dose was commonly used, with doses ranging from 10 mg/kg [14,15,18,[20][21][22] to 100 mg/kg [16], usually infused over 15 minutes after induction of general anesthesia and before skin incision. A continuous infusion until skin closure was performed in all studies, with different protocols: 5 mg/kg/h [10,14,18,[20][21][22][23] or 10 mg/kg/h [9,16,17,19,24].…”
Section: Analysis Of Protocolsmentioning
confidence: 99%
See 1 more Smart Citation